Parlante superdireccional de matriz paramétrica - Montes de Oca, Axel (2019)
In this work, a directional loudspeaker, also known as a parametric array loudspeaker (PAL), is designed and constructed. The operation is based on the phenomenon called self-demodulation that happens when high-frequency beams interact in a viscous medium, due to its non-linear properties. The sound obtained after the self-demodulation is formed in the beam of the ultrasonic carrier signal propagating beyond the absorption distance in which the carrier has been sufficiently attenuated. This generates a focused audible signal and therefore a directional polar pattern of narrow angle. In this paper two modulation methods are evaluated: double-sideband amplitude (AM-DBL) and pulse-width modulation (PWM). Its effect on directionality, sound pressure level and harmonic distortion is experimentally analyzed.